Tsetse Invasion as an Emerging Threat to Socioecological Resilience of Pastoral Communities in Karamoja, Uganda - Egeru, Anthony; Opio, Joseph; Siya, Aggrey; Barasa, Bernard; Magaya, John Paul; Namaalwa, Justine J. (Sustainability, 2020)
Over 70% of Uganda is infested by the tsetse fly, which has negative e ects on human and livestock health. From colonial to post-independent Uganda, the Government of Uganda has worked to eradicate the tsetse menace. Despite these e orts, recent veterinary reports from the Karamoja sub-region have indicated widespread tsetse invasion. This study investigated the potential impact of tsetse invasion on the socioecological resilience of pastoral communities in the Karamoja sub-region. Results indicated that tsetse invasion is spreading from north to south of Karamoja. The tsetse transmission route emerging from southern Karamoja is perceived to be a continuation of the tsetse belt from West Pokot, Kenya. Cases of livestock deaths, livestock abortions, decreased milk yields, restricted access to prime grazing lands, heightened human-wildlife conflicts and disruption on crop cultivation have been reported. A computed socioecological resilience index in the study area was positive but low. Owing to the transboundary characteristics of tsetse invasions and sources and the associated documented e ects, an urgent, strategic and system-wide intervention should be undertaken to control the tsetse invasion in this sub-region.
Keywords: Glossina spp.; Health; Sleeping sickness; Tsetse invasion; Karamoja sub-region; Africa